Sovereign rating changes and the impacts on short-term emerging market financial stability - Shahrivar, Hesam Aldin (National Academy of Management eco@nam.kiev.ua Vul. Panasa Myrnogo, 26 Kyiv 01011, 2013)
This study aims to investigate the relationship between sovereign rating announcements and financial markets. In particular, this study examines the role of sovereign rating changes in the view of fluctuations at financial markets. The empirical analysis of 25 emerging market economies is done using the index of speculative market pressure, created on the basis of weighted average of main financial indices (i.e., interest rate, exchange rate, and capital market index). ARMA model is then used to compute the abnormal jumps in the produced financial index. Thereafter an event study has been done to test for significance of any impact of rating changes on the speculative market pressure index. The empirical results indicate that credit rating agencies have significant short-term effects on financial markets. Market indicators apparently are highly sensitive to the announcements made by credit rating agencies, and their impact is greatly amplified when there is a downgrade rather than when there is an upgrade. © Hesam Aldin Shahrivar, 2013.
Keywords: ARMA model; Emerging economies; Event study; Sovereign credit rating